Molecular marker associated with a deleterious recessive anomaly in Eucalyptus grandis seedlings - Fuchs, Maria C. P. [UNESP]; Tambarussi, Evandro V.; Lourenção, Juliana C. [UNESP]; Nogueira, Letícia M.; Bortoloto, Tânia M. [UNESP]; González, Esteban R.; Oda, Shinitiro; Marino, Celso L. [UNESP] (Springer Nature, 2015)
Key message: The identification of an anomaly with deleterious effect and Mendelian segregation (3 normal: 1 abnormal) allowed the detection of a marker linked to a locus for the anomalous phenotype. This marker could be useful in marker-assisted breeding programs and for understanding this anomaly. Context: Due to the mixed mating systems in Eucalyptus genera, outcrossing populations exhibit low inbreeding depression (abnormalities). In this study, we identified a developmental anomaly in a controlled cross of Eucalyptus grandis, with Mendelian segregation. The anomaly was characterized by branching, reduced height, smaller individual leaf area, and asymmetrical leaf shape. Aims and methods: To investigate and evaluate the anomaly detected, we performed morphological and molecular analysis. The genitors and bulks of normal and abnormal individuals were screened with random primers. The polymorphic markers that co-segregated with the anomalous phenotype were selected, validated, converted into SCAR markers and analyzed in silico. Results: Morphological analysis showed significant differences between normal and abnormal phenotypes. The co-segregating marker was present in one genitor, in all abnormal individuals, and in 31 % of normal individuals (recombinants). In silico analyses revealed a mutation of two base pairs between the contrasting phenotypes and identified the marker in an intergenic region presenting partial identity with an expressed sequence tag (EST) of Bet v1-like genes. Conclusion: A marker was developed to identify the recessive allele for the anomaly in E. grandis. This will be important for management of crosses in eucalypt breeding programs and in anomaly studies.
Keywords: Deleterious recessive alleles; Eucalypt anomaly; Eucalypt development; Molecular marker